Online Guest Book Application for Computer Science Department at Bina Bangsa University - Permana, Basuki Rakhim Setya; Auliana, Sigit; Rohman, Ali; Munawir, Ahmad; Mulyawansyah, Ahmad Andika (ARRUS Journal of Engineering and Technology, 2024)
Information technology is currently useful for automating various processes and activities that were previously done manually. Now human activities are turning into computerized systems. Information that is presented quickly and precisely greatly influences the level of work efficiency and effectiveness in various fields. This research uses the waterfall method, which is a software development process model which is a sequential and linear approach. This approach relies on sequential and progressive stages, where each stage must be completed before entering the next stage. Based on the results of the research and discussions that have been carried out, it can be stated that with this web-based guest book application, it is hoped that the input, data collection and recording processes can be more effective and efficient and the security of data storage will be more guaranteed